Affective and Perceptual Responses During an 8-Week Resistance Training to Failure Intervention at Low vs. High Loads in Untrained Women. Issue 3 (4th March 2023) - Anderson, Olivia K.; Voskuil, Caleb C.; Byrd, M. Travis; Garver, Matthew J.; Rickard, Alex J.; Miller, William M.; Bergstrom, Haley C.; Dinyer McNeely, Taylor K.
Abstract: Anderson, AlOK, Voskuil, CC, Byrd, MT, Garver, MJ, Rickard, AJ, Miller, WM, Bergstrom, HC, and Dinyer McNeely, TK. Affective and perceptual responses during an 8-week resistance training to failure intervention at low vs. high loads in untrained women. J Strength Cond Res 37(3): 546–554, 2023—This study examined the effects of resistance training (RT) to failure on the perceptual and affective responses, intent-to-continue RT to failure in a self-initiated session, and affect-intent relationship. Twenty-three untrained women (mean ± SD : age 21.2 ± 2.2 years; height 167 ± 5.7 cm; body mass, 62.3 ± 16.2 kg) completed an 8-week, full-body RT to failure intervention at a low (30% 1RM; n = 11) or high (80% 1RM; n = 12) load. The Borg's rating of perceived exertion (RPE) scale was used to assess the acute (aRPE) and session (sRPE) RPE immediately after repetition failure and each training session, respectively. Immediately, 15-minute, and 60-minute postsession affective responses were assessed using the feeling scale (FS; −5 to +5), and intent to continue to RT was assessed on a scale of 0–100% intention. During week 4 (W4) and week 8 (W8), aRPE (W4: 18 ± 2, W8: 18 ± 2; p ≤ 0.032) and sRPE (W4: 17 ± 2, W8: 18 ± 1; p ≤ 0.018) were greater than that during week 1 (W1; aRPE: 17 ± 2; sRPE: 16 ± 2). The FS responses increased from immediately to 60-minute postsession during W4 ( p ≤ 0.019) and W8 ( p ≤ 0.049). The correlation between affect and intent-to-continue RT increased from W1 ( r = 0.416) to W8 ( r = 0.777). Regardless of load, untrained women reported similar perceptual, affective, and intention responses. These variables should be considered to improve RT program adoption and adherence in women.